Evaluation of the Ecological Security and Tourism Vulnerability in the Hara Protected Area - Parvaneh Sobhani; Afshin Danehkar (محیط زیست و توسعه فرابخشی)
Introduction: The ecological security of tourism provides a new research framework and practical tools for analyzing sustainable regional development. This facilitates the development of high-quality tourism and also protects natural ecosystems. Therefore, ecological security plays an important role in examining biological resources about society, economy, and environment and, especially concerning protected areas, can provide vital information for habitat conservation and conservation strategies. This study aimsto assess the ecological security of tourism based on the establishment of a driver framework and pressures in the Hara protected area.Materials and Methods: In the present study, the ecological security and vulnerability of tourism were assessed based on the DPSIR model framework in the Hara protected area. Accordingly, by considering five key factors ("Driver", "Pressure", "State", "Impact", "Response"), the effective indicators on the ecological security of tourism were examined and analyzed in this protected area. For this purpose, a list of effective indicators that can affect the ecological security of tourism was prepared based on previous documents and studies and according to the opinions of specialists and experts.Results: The results revealed that the highest ecological security of tourism is visible in the east of Khorkhoran island and the west of Sayeh Khosh habitat, especially in the central areas of mangrove forests, and in contrast, the lowest level is related to the north and south of the area around Marduv island, Khamir Lashtqan and coastal Qeshm due to the expansion of various human activities. In addition, the results of the classification of ecological tourism security showed that the Hara protected area has 68.56 percent of the ecologically safe tourism class and 32.43 percent of the unsafe class. The evaluation of the indicators affecting the ecological security of tourism also indicates that the highest score among the "drivers" is related to the increase in construction with a value of 64.3, among the "pressures" is the index of excessive harvesting of branches and feeding of wandering camels with a value of 88.4, among the "state" indicators is the level of vegetation density with a value of 22.3, among the "responses" coefficients is the prevention of branching and provision of fodder for livestock (especially camels) with a value of 18.3. According to the results, the status index in the mangrove forests of the island and the Khorkhoran Strait has the lowest value due to the limited development of human activities, while the highest state index is observed in the north, south of the region and the centers of human activity development. Also, the highest impact index is related to the surroundings of ports, commercial and tourist piers, coastal areas and tourism development centers. Accordingly, in areas that are the centers of human activity development, the driving, pressure and impact indices have increased, resulting in a decrease in ecological security in the region.Discussion: Based on the results obtained, the most threats to the ecological security of tourism are related to uncontrolled human activities and also insufficient supervision over the development and exploitation of ports and piers in the region. Therefore, controlling these pressures and threats requires integrated planning and management at the regional level. In this regard, the results of this study can help decision-makers and planners in developing a management plan and taking strategic measures in this area by providing a range of key factors and indicators affecting the ecological security of tourism in the Hara protected area.